Insights into families of children with selective mutism - Romić, Ivona; Šimleša, Sanja; Olujić Tomazin, Marina; Ivšac Pavliša, Jasmina (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Selective mutism (SM) is an anxiety disorder marked by persistent failure to speak in specific social situations despite normal speech in others. Research suggests a multifactorial aetiology involving temperament, genetic, neurodevelopmental, and environmental influences, with families playing a significant role. Aim. This study examined parental personality traits and family environmental factors in 30 mothers of children with SM. Method. Data were collected using a structured questionnaire and the IPIP-NEO-120 inventory. Results. Parents most often described themselves in childhood as quiet, shy, or withdrawn, traits commonly observed in their children. On the personality scale, they scored highest on agreeableness and conscientiousness and lowest on neuroticism. Families were described as sociable but primarily within close family circles. Nearly three-quarters of children had experienced at least one environmental risk factor, most often relocation. Conclusion. Findings highlight the importance of familial characteristics in understanding SM and suggest implications for targeted support and intervention.